Acetylated Histones in Apoptotic Microparticles Drive the Formation of Neutrophil Extracellular Traps in Active Lupus Nephritis - Rother, Nils; Pieterse, Elmar; Lubbers, Jelle; Hilbrands, Luuk; van der Vlag, Johan (Frontiers in Immunology, 2017)
Objective: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the presence of autoantibodies against nuclear components. Lupus nephritis (LN) is the major cause of morbidity and mortality in patients with SLE. Central to the pathogenesis of SLE is the accumulation of cellular waste, especially apoptotic microparticles (MPs), which stimulates diverse immune reactions including the formation of neutrophil extracellular traps (NETs). In this study, we investigated the content of MPs from SLE patients with and without (active) LN, their capacity to stimulate NET release and assessed the molecular mechanisms underlying MP-induced NETosis. Methods: MPs from SLE patients with biopsy-proven active LN, remissive LN, without LN and healthy controls were characterized by flow cytometry. Isolated neutrophils were exposed to MPs derived from either patient plasma or apoptotic human umbilical vein endothelial cells, and NET release was quantified by immunofluorescence imaging, spectrofluorometry or an in-house developed NET-ELISA. Results: MPs from SLE patients with active LN contain higher levels of acetylated chromatin compared to MPs from those with remissive LN, without LN or healthy controls. MPs enriched in hyperacetylated chromatin are more potent in inducing NETosis when compared to MPs containing moderate acetylated chromatin. The release of NETs in response to MPs occurs rapidly in a concentration-dependent manner and proceeds independent from the formation of reactive oxygen species. Conclusion: Our data suggest that MPs containing acetylated chromatin drive ROS-independent NET release in SLE patients with active LN, which may lead to the glomerular deposition of NETs and subsequent NET-driven lupus nephritis.